Pengaruh Rekrutmen Dan Seleksi Terhadap Kinerja Karyawan Di PT Cisarua Mountain Dairy Tbk Sentul - Ignasius Moses Julianto Sitohang; Hira Maulida (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to examine the effect of recruitment and selection on employee performance at PT Cisarua Mountain Dairy Tbk Sentul. The research employed a quantitative approach with a sample of 55 respondents. Data were collected through questionnaires and analyzed using simple and multiple linear regression. The results show that partially, recruitment has a positive and significant effect on employee performance with the regression equation Y = 7.299 + 0.715X, a t-value of 7.752, and a significance level of 0.000 < 0.05. The correlation coefficient of 0.729 indicates a strong relationship, with a coefficient of determination (R²) of 53.1%. Selection also has a positive and significant effect on employee performance with the regression equation Y = 9.122 + 0.709X, a t-value of 10.846, and a significance level of 0.000 < 0.05. The correlation coefficient of 0.830 indicates a very strong relationship, with an R² value of 68.9%. Simultaneously, the multiple regression analysis produced the equation Y = 6.165 + 0.193X₁ + 0.576X₂. The selection variable has a significant effect (0.000 < 0.05), while recruitment is not significant (0.113 > 0.05). The F-test result of 61.889 with a significance level of 0.000 < 0.05 indicates that recruitment and selection simultaneously have a significant effect on employee performance. The correlation coefficient (R) of 0.839 shows a very strong relationship, with a combined contribution of 70.4%..